Analysis of free amino acids in flue‐cured tobacco leaves using ultra‐high performance liquid chromatography with single quadrupole mass spectrometry. Issue 17 (30th July 2013) - Zhang, Junjie; Zhao, Chunxia; Chang, Yuwei; Zhao, Yanni; Li, Qinghua; Lu, Xin; Xu, Guowang; Svec, Frantisek
<x xml:space="preserve">Abstract</x> Amino acids are one of the most important metabolites of organisms. They play an important role in plant growth, development, and product quality. A method based on RP ultra‐performance LC with single quadrupole MS and 6‐aminoquinolyl‐N‐hydroxysuccinimidyl carbamate precolumn derivatization was developed for the analysis of free amino acids in flue‐cured tobacco leaves. Unlike the corresponding UV detection method, this method avoids matrix interference of complicated tobacco components, and the quantitative accuracy and resolution were improved. Twenty free amino acids were detected in flue‐cured tobacco leaves. The method showed a good linearity with correlation coefficients of 0.9966–0.9998. The LODs for derivatized amino acids were 0.2–9.7 fmol/μL. Good repeatability with an RSD of 2.5–8.6% and satisfactory intra‐ and interday precisions were obtained. The developed method was used to investigate free amino acids in flue‐cured tobacco leaves in China. The effects of aroma type, variety, and growing regions on free amino acids were investigated. The results showed that free amino acids in tobacco were affected by growing regions and varieties.